2016
DOI: 10.1155/2016/5768526
|View full text |Cite
|
Sign up to set email alerts
|

FoodborneListeria monocytogenes: A Real Challenge in Quality Control

Abstract: Listeria monocytogenes is a foodborne pathogen, and the detection and differentiation of this bacterium from the nonpathogenic Listeria species are of great importance to the food industry. Differentiation of Listeria species is very difficult, even with the sophisticated MALDI-TOF MS technique because of the close genetic relationship of the species and the usual gene transfer. The present paper emphasizes the difficulties of the differentiation through the standardized detection and confirmation according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The result is in agreement with the findings of Cetinkaya et al (2014) who reported 30% and 32% by Alvarez-Ordoriez et al (2015) but lower than 71% recorded by Eklund et al (1995) and 88% recorded by Ieren et al (2013). More so, the result were higher than 15% reported by Johansson et al (1999), 17% by Fonnesbech-Vogel et al (2001, 1% by Hoffman et al (2003) and 3% by Pusztahelyi et al (2016). The differences in the values might be attributed the management practices such as cleaning.…”
Section: Discussionsupporting
confidence: 91%
“…The result is in agreement with the findings of Cetinkaya et al (2014) who reported 30% and 32% by Alvarez-Ordoriez et al (2015) but lower than 71% recorded by Eklund et al (1995) and 88% recorded by Ieren et al (2013). More so, the result were higher than 15% reported by Johansson et al (1999), 17% by Fonnesbech-Vogel et al (2001, 1% by Hoffman et al (2003) and 3% by Pusztahelyi et al (2016). The differences in the values might be attributed the management practices such as cleaning.…”
Section: Discussionsupporting
confidence: 91%
“…Pusztahelyi et al reported that more than half of the tested bacterial strains (n = 18) were scored with values that gave secure identification only at the genus level (2.000–2.299), while only seven strains gave a highly probable species identification (>2.300). Furthermore, the same study showed the misidentification of L. monocytogenes at the species level [ 19 ]. In contrast, Thouvenot et al reported the complete reliability of MALDI-TOF MS mass spectrometry to identify Listeria in human, animal, food and environmental microbiology, with 100% accuracy for identifying eight species, including L. monocytogenes [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This technique enabled the identification of L. monocytogenes with 100% accuracy, regardless of its origin, whether from humans, animals, food or the environment [ 16 , 17 ]. On the other hand, other authors have shown that the MALDI-TOF MS method is not without limitations in identifying L. monocytogenes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…What should now be considered in retrospect is the demanding nature of the microbiological reference method, for example, ISO 11290-1, concerning the differentiation of L. innocua and L. monocytogenes [59]. Reports focusing on the challenges associated with Listeria detection and confirmation are available, including atypical strains or L. monocytogenes present in lower concentrations due to competitive L. innocua strains during enrichment or that mask detection of L. monocytogenes on selective agar plates such as ALOA medium [60,61] (https://www.fda.gov/food/laboratory-methodsfood/guidelines-bam-users-identification-atypical-hemolytic-listeria-isolates). This might also have contributed to a higher isolation rate of L. innocua compared to L. monocytogenes in our study.…”
Section: Discussionmentioning
confidence: 99%